Camping out - Mayer, Mercer, 1943- (Columbus, Ohio : McGraw-Hill Children's Pub., 2002)
When Little Critter and Gator camp out in the backyard, strange noises bother them until they discover that there is a harmless explanation for each one. Includes activities.
"Level 1, Grades PreK-K."
"Mercer Mayer's Little Critter"--Cover.
Keywords: Camping -- Fiction; Fear -- Fiction; Sound -- Fiction